The long-term outcome after axillo-axillary bypass grafting for proximal subclavian artery disease. - Perkins, J; Magee, T; Hands, L; Collin, J; Morris, P (2000)
OBJECTIVES: to investigate the outcome of patients undergoing axillo-axillary bypass grafting for symptomatic subclavian artery stenoses or occlusions. DESIGN: retrospective case-note review and prospective review of patients available for follow-up. PATIENTS AND METHODS: sixteen patients had axillo-axillary grafts in a 17-year period. Ten patients were available for review and assessed clinically, by measurement of arm blood pressures, and by duplex scanning of their grafts. RESULTS: one patient died and three grafts occluded within 30 days of operation. Nine out of 10 grafts scanned were patent, with three further grafts clinically patent at death. Overall secondary patency was 75% at a combined median follow-up of 56 months (range 12-204 months). Recurrent symptoms occurred in two patients, one with an occluded graft and one with a patent graft. CONCLUSION: axillo-axillary bypass grafts give good long-term symptom-free results.